2008
DOI: 10.1016/j.juro.2008.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Following Active Surveillance of Men With Localized Prostate Cancer Diagnosed in the Prostate Specific Antigen Era

Abstract: Men with low grade prostate cancer can elect active surveillance and have excellent long-term results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 16 publications
0
55
0
3
Order By: Relevance
“…Eight non-comparative studies of low-risk patients undergoing active surveillance reported prostate cancer survival rates of 100% [5][6][7][8][9][10][11][12] and another two non-comparative studies reported high prostate cancer survival rates of 97% 13 98%, respectively. 14 Studies comparing immediate RP with delayed RP in patients undergoing AS detected no significant differences in biochemical recurrence rate, positive surgical margins, extraprostatic extension, [15][16][17] and risk of incurable cancer.…”
Section: Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight non-comparative studies of low-risk patients undergoing active surveillance reported prostate cancer survival rates of 100% [5][6][7][8][9][10][11][12] and another two non-comparative studies reported high prostate cancer survival rates of 97% 13 98%, respectively. 14 Studies comparing immediate RP with delayed RP in patients undergoing AS detected no significant differences in biochemical recurrence rate, positive surgical margins, extraprostatic extension, [15][16][17] and risk of incurable cancer.…”
Section: Recommendationmentioning
confidence: 99%
“…[5][6][7][8][9][12][13][14][15][16][18][19][20][21][22]29,32,33 The studies reporting their active surveillance protocol conducted multicore (6-to 17-core) biopsies every 1 to 2 years. 5,10,12,[15][16][17][18]21,23,[28][29][30][33][34][35] Five studies conducted multicore biopsies every 2 to 4 years. 8,11,13,19,32 Regarding Multiparametric MRI, it has been shown to be a good predictor of disease reclassification.…”
Section: Recommendationmentioning
confidence: 99%
“…AS programmes have been initiated to acquire evidence for the currently used selection and surveillance criteria, which are based on retrospective data [6][7][8][9][10][11]. The 'Prostate Cancer Research International: Active Surveillance (PRIAS) study [12] is an international prospective observational study originating from the European Randomized Study of Screening for Prostate Cancer (ERSPC) [13].…”
Section: Introductionmentioning
confidence: 99%
“…The prostate cancer is the most common malign visceral neoplasia in men and the incidence tends to increase in coming decades with the increase in life expectancy (14,24,37) . Approximately 543 thousand new cases are diagnosed each year worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Histological and serological exams describe very important aspects, allowing the monitoring of the disease evolution (3,16) . However, the immuno-histochemical methods as discussed in qualitative form have shown great disparity and variability of results among different observers (13,14,30) . In order to provide a numerical scale and reproducible patterns of marking tissue, increasing the sensitivity and quality control analysis, it has sought increasingly technological refinements using automated morphometric methods (12) .…”
Section: Introductionmentioning
confidence: 99%